Critical Regimes of Two-Phase Flows with a Polydisperse Solid Phase - Barsky, Eugene; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This book brings to light peculiarities of the formation of critical regimes of two-phase flows with a polydisperse solid phase. A definition of entropy is formulated on the basis of statistical analysis of these peculiarities. The physical meaning of entropy and its correlation with other parameters determining two-phase flows are clearly defined. The interrelations and main differences between this entropy and the thermodynamic one are revealed. The main regularities of two-phase flows both in critical and in other regimes are established using the notion of entropy. This parameter serves as a basis for a deeper insight into the physics of the process and for the development of exhaustive techniques of mass exchange estimation in such flows. The book is intended for graduate and postgraduate students of engineering studying two-phase flows, and to scientists and engineers engaged in specific problems of such fields as chemical technology, mineral dressing, modern ceramics, microelectronics, pharmacology, power engineering, thermal engineering, etc. using flows with solid particles in their respective production methods.
General Ideas of Mass Transfer Processes in Critical Regimes -- Principles of Modeling Processes in Moving Media -- System of Particles of the Same Size Class in a Critical Flow -- System of Particles of Several Size Classes -- Principal Statistical Relations of Mass Transfer in Critical Flow -- Correlation Between the Apparatus and the Cell -- Structural Model of Mass Transfer in Critical Regimes of Two-Phase Flows -- Correlation Between Statistical and Empirical Results -- Entropy of Composition: Optimization Criterion -- Stability and Kinetic Aspects of Mass Distribution in Critical Regimes -- Critical Regimes of Two-Phase Flows in Complicated Systems -- Stochastic Model of Critical Regimes of Two-Phase Flows -- Mass Transfer in Critical Regimes of Two-Phase Flows -- Universal Curves Criteria.
Keywords: Engineering; Chemical engineering; Mathematical optimization; Hydraulic engineering; Engineering; Engineering Fluid Dynamics; Soft and Granular Matter, Complex Fluids and Microfluidics; Mathematical Modeling and Industrial Mathematics; Industrial Chemistry/Chemical Engineering; Optimization